Primary school bullying: Factors, forms and solutions - Ihsan, Muhammad Aidi Noor; Sukriono, Didik; Pristiani, Riska; Kusumaningrum, Shirly Rizki (Univeritas Papua, 2024)
This research is motivated by the rampant cases of bullying in schools caused by various factors and forms of bullying behavior played by students in schools. This study describes the forms, factors, and solutions the school has implemented. The researcher used a descriptive qualitative method to write the findings. Data collection was carried out using interviews, observations, and filling out questionnaires. The results illustrate that bullying behavior that occurs at school can be verbal by mocking, insinuating, and instigating. While social bullying, such as ostracising friends. In response, primary schools in Malang City formed an anti-bullying task force to minimize bullying and educate students regarding it in the school environment. The task force's role is to educate (remind) what bullying is for all students in the school and to model positive behavior (role model).